2008
DOI: 10.1037/0022-3514.95.3.576
|View full text |Cite
|
Sign up to set email alerts
|

Coordination success and interpersonal perceptions: Matching versus mismatching.

Abstract: Coordination is an essential part of social functioning. The authors distinguish 2 types of coordination: matching and mismatching. In matching, coordination is successful if parties choose the same action. In mismatching, coordination is successful if people choose different actions. In 3 studies, the authors investigated the downstream social consequences of tacit coordination for interpersonal perceptions. In all studies, participants repeatedly choose between 2 bets with equivalent expected values, and pay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 24 publications
3
33
0
Order By: Relevance
“…Abele and Stasser (2008) demonstrated that matching and mismatching coordination are different on several dimensions. In general, mismatching problems are more difficult and often require more detailed social knowledge to succeed than do matching problems (Abele, Stasser, & Chartier, 2014;Chartier & Abele, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Abele and Stasser (2008) demonstrated that matching and mismatching coordination are different on several dimensions. In general, mismatching problems are more difficult and often require more detailed social knowledge to succeed than do matching problems (Abele, Stasser, & Chartier, 2014;Chartier & Abele, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, normative preferences among the group members or exhibited by highstatus members (leaders) can be used to guide action in ambiguous situations. Abele and Stasser (2008) showed that people were quite good at coordinating actions around social focal points, and successful coordination led to greater liking among group members. More recent research (Abele and Chartier, 2012) has shown that groups are substantially better than individuals at locating and using social focal points.…”
Section: Structural and Social Focal Pointsmentioning
confidence: 98%
“…It appears that humans may have learned to use structural characteristics of their environments to help to coordinate action (e.g., meeting in the center of the village or at the water's edge). More recent research has shown that 'social focal points' are also useful in coordinated action (Abele and Stasser, 2008). Thus, normative preferences among the group members or exhibited by highstatus members (leaders) can be used to guide action in ambiguous situations.…”
Section: Structural and Social Focal Pointsmentioning
confidence: 99%
“…An important step forward in our understanding of how players' traits may impact tacit coordination decisions was taken when the categorization of problems into matching and mismatching coordination was recognized as an important distinction for identification of focal points (Abele & Stasser, 2008). They argued that a matching focal point can occur simply due to one option's popularity, as seen in Mehta and colleagues work (1994); however salience differences among options do not define a mismatching focal point.…”
Section: Explored This Intuition In His Now Classic Book the Strategymentioning
confidence: 99%
“…To fully understand the use and effectiveness of this social information one must consider two key factors: the standing of each dyad member on the relevant trait and the specific coordination task requirement. Specifically, whether the dyad is similar or different on the relevant trait, and whether the task requires coordination by matching or mismatching (Abele & Stasser, 2008). The coordinating parties' standing on the relevant construct must map on to the coordination requirement in order to promote coordination efficiency.…”
Section: Explored This Intuition In His Now Classic Book the Strategymentioning
confidence: 99%